IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN BAHASA INDONESIA: STUDI PUSTAKA - Puspa Sari, Lala; Andra, Vebbi; Friantary, Heny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Differentiated instruction is one of the main pillars of the Merdeka Curriculum, designed to accommodate the diversity of students’ characteristics, interests, and readiness to learn. This study aims to analyze the implementation of differentiated instruction specifically in the Indonesian Language subject through a literature review approach. The method used is content analysis of various relevant scientific articles from Google Scholar published between 2020 and 2026. The results of the study indicate that the implementation of differentiated instruction in the Indonesian Language subject is carried out through three main strategies: content differentiation (text/non-text instructional materials), process differentiation (reading and writing strategies), and product differentiation (variations in language performance forms). The main supporting factors include teacher creativity and the availability of instructional modules, while the inhibiting factors are limited planning time and classroom management. This study concludes that differentiated instruction effectively improves language skills and active engagement among students.